1992
DOI: 10.2307/2409640
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Alcohol Dehydrogenase Activity and Flood Tolerance in White Clover, Trifolium repens

Abstract: Hooding results in induction of anaerobic metabolism in many higher plants. As an important component of anaerobic energy production, alcohol dehydrogenase (ADH) activity increases markedly in response to flooding in white clover, Trifolium repens. Significant interindividual variation in flood-induced ADH activity exists in natural populations of T. repens. The genetic basis of this variation was analyzed by offspring-rnidparent regression of data from 75 greenhouse reared families; the estimated heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…13,22 Activities of these enzymes may be important in fruit tolerance to anaerobic conditions as indicated for other plant systems, eg variation in ADH activity accounted for more than 79% of¯ooding tolerance in individuals of natural populations of Trifolium repens. 23 ADH and AAT also have important roles in development of strawberry volatiles during normal ripening. 22,24 Differences in volatile accumulation under high CO 2 partial pressures may be related to naturally occurring variation in the activities of these enzymes and their isozymes during normal fruit development among cultivars.…”
Section: Volatilesmentioning
confidence: 99%
“…13,22 Activities of these enzymes may be important in fruit tolerance to anaerobic conditions as indicated for other plant systems, eg variation in ADH activity accounted for more than 79% of¯ooding tolerance in individuals of natural populations of Trifolium repens. 23 ADH and AAT also have important roles in development of strawberry volatiles during normal ripening. 22,24 Differences in volatile accumulation under high CO 2 partial pressures may be related to naturally occurring variation in the activities of these enzymes and their isozymes during normal fruit development among cultivars.…”
Section: Volatilesmentioning
confidence: 99%
“…Intraspecific differentiation has been previously reported. Chan and Burton (1992) found that seeds of Trifolium repens from a site constantly challenged by flooding presented higher flood tolerance, while seeds from a site without flooding history presented lower flood tolerance. Lessen et al (2004) showed that flooding induces genetic variation within Ranunculus reptans populations on a small spatial scale.…”
mentioning
confidence: 92%
“…1997) overrides the impact of selection. A number of studies have indicated that there is genetic variation within species in all of the physiological traits mentioned above, suggesting that there is the potential for selection (Linhart & Baker 1973; Keeley 1979; Chan & Burton 1992; Robe & Griffith 1998; Lynn & Waldren 2002, 2003). Moreover, genetic differentiation in these traits has been found over a small spatial scale along flooding gradients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2000). In Trifolium repens , seed families with higher ADH (alcohol dehydrogenase) activities during flooding had greater flood tolerance (Chan & Burton 1992), and seed families from a site without flooding history had lower ADH levels than those from a frequently flooded site. However, we are not aware of any well‐replicated study that has tested for local within‐population adaptation in response to flooding.…”
Section: Introductionmentioning
confidence: 99%